LEAF AREA OF Erythrina velutina Willd. (FABACEAE) THROUGH ALLOMETRIC EQUATIONS - Ribeiro, João Everthon da Silva; Figueiredo, Francisco Romário Andrade; Nóbrega, Jackson Silva; Coêlho, Ester dos Santos; Melo, Marlenildo Ferreira (Floresta, 2022)
Leaf area estimation is of fundamental importance to evaluate growth, development, and propagation of plants. This work aimed to adjust and identify regression models to estimate leaf area of Erythrina velutina from linear dimensions of the central leaflet of leaves. Two hundred simple leaves were collected from E. velutina mother plants in forest fragments in the municipality of Mossoró, Rio Grande do Norte state, Northeast Brazil. The equation for estimating leaf area of E. velutina was adjusted from linear, linear without intercept (0.0), quadratic, cubic, power, and exponential regression models. The best equations were those with the highest determination coefficient (R²), Pearson's correlation coefficient (r), Willmott's index (d) and CS index (CS), and with the lowest Akaike information criterion (AIC), mean absolute error (MAE), root mean square error (RMSE), and BIAS index closest to zero (BIAS). The equations fitted using the product of length by width (LW) showed the best criteria for estimating leaf area, thus best fitting the regression models used. Therefore, the equation ŷ = 1.4755*LW adjusted using the linear model without intercept is the most suitable for estimating leaf area of E. velutina (R² = 0.9906; r = 0.9860; d = 0.9929; CS = 0.9790; AIC = 1402.7; MAE = 5.34; RMSE = 7.90; BIAS = 0.019).